High capacity flexible fibrous zinc ion battery and method of making the same
Patent Information
- Application Number
- CN202310704541.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-14
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-06-14
AI Technical Summary
[0004]本申请的目的在于提供一种高容量柔性纤维状锌离子电池及其制备方法,以解决现有技术中存在的传统的柔性锌离子电池容量低的问题,无法满足柔性电子设备的需求的技术问题
[0030]1、本申请使用溴对碳纳米管纤维进行改性处理,有效提高了碳纳米管纤维的导电性和机械强度,有助于提高电池的容量;
Smart Images

Figure CN116646618B_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of zinc-ion battery technology, specifically relating to a high-capacity flexible fibrous zinc-ion battery and its preparation method. Background Technology
[0002] With the rapid development of various portable and wearable electronic devices, the development of novel flexible energy storage devices has become a hot topic in scientific research. Research on high-performance, bend-resistant batteries is key to the development of wearable electronic products. Smart wearable devices and integrated electronic products need to meet the requirements of shape diversity and mobility, such as flexible displays, flexible electronic skin, smart electronic clothing, microelectromechanical systems, and other diverse applications. Flexible electronic devices are developing towards miniaturization and lightweighting.
[0003] Among various water-based energy storage devices, zinc is abundant and inexpensive. Furthermore, new rechargeable zinc-ion batteries (ZIBs) use neutral zinc salts as electrolytes, which are not only simple to manufacture and lower in cost, but also safe, non-toxic, and have a high specific capacity. This avoids the flammability and explosion risks of traditional lithium batteries, making them a better choice for flexible electronic devices. However, traditional flexible zinc-ion batteries have the problem of low capacity, which cannot meet the needs of flexible electronic devices. Summary of the Invention
[0004] The purpose of this application is to provide a high-capacity flexible fibrous zinc-ion battery and its preparation method, so as to solve the technical problem that the traditional flexible zinc-ion battery has low capacity and cannot meet the needs of flexible electronic devices.
[0005] To achieve the above objectives, one technical solution adopted in this application is:
[0006] A method for preparing a high-capacity flexible fibrous zinc-ion battery is provided, comprising:
[0007] Modified carbon nanotube fibers were obtained by modifying carbon nanotube fibers with bromine.
[0008] A negative electrode active material is electrodeposited on the surface of the modified carbon nanotube fibers to obtain a fibrous negative electrode;
[0009] A positive electrode active material was deposited on the surface of the modified carbon nanotube fibers using a hydrothermal method to obtain a fibrous positive electrode.
[0010] A gel electrolyte is coated onto the surfaces of the fibrous negative electrode and the fibrous positive electrode, respectively.
[0011] A bundle structure is formed by twisting and winding several fibrous negative electrodes coated with the gel electrolyte and several fibrous positive electrodes coated with the gel electrolyte together. The bundle structure includes a first end and a second end arranged opposite to each other. One end of the fibrous positive electrode extends out of the first end to form a positive electrode connector, and one end of the fibrous negative electrode extends out of the second end to form a negative electrode connector.
[0012] The high-capacity flexible fibrous zinc-ion battery is obtained by covering the outer surface of the bundle-like structure with an encapsulation layer.
[0013] In one or more embodiments, the step of electrodepositing the negative electrode active material on the surface of the modified carbon nanotube fibers to obtain a fibrous negative electrode includes:
[0014] The modified carbon nanotubes are immersed in an electrolyte solution containing zinc sulfate and sodium sulfate, and metallic zinc is deposited on the surface of the modified carbon nanotubes under the action of an external electric field to obtain the fibrous negative electrode.
[0015] In one or more embodiments, the concentration of zinc sulfate in the electrolyte solution is 0.5–3 mol / L, the concentration of sodium sulfate is 0.1–1 mol / L, and the current density of the external electric field is -10 to -50 mA / cm². 2 .
[0016] In one or more embodiments, the step of depositing the positive electrode active material on the surface of the modified carbon nanotube fibers using a hydrothermal method to obtain a fibrous positive electrode includes:
[0017] An aqueous solution containing potassium permanganate and concentrated hydrochloric acid was added to a high-pressure reactor. The modified carbon nanotubes were then immersed in the aqueous solution and reacted in an oven. After the reaction was completed, the mixture was cooled to room temperature and then washed and dried sequentially to obtain a fibrous positive electrode.
[0018] In one or more embodiments, the mass concentration of potassium permanganate in the aqueous solution is 1-10 g / L, the volume concentration of concentrated hydrochloric acid is 0.3-5.1%, the reaction temperature in the oven is 60-80°C, and the reaction time is 15-60 min.
[0019] In one or more embodiments, the gel electrolyte is a mixed solution comprising sodium carboxymethyl cellulose and zinc sulfate, wherein the concentration of sodium carboxymethyl cellulose in the gel electrolyte is 0.05–0.2 g / mL and the concentration of zinc sulfate is 0.1–0.3 g / mL.
[0020] In one or more embodiments, the step of twisting and winding a plurality of fibrous negative electrodes coated with the gel electrolyte and a plurality of fibrous positive electrodes coated with the gel electrolyte to form a bundle structure includes:
[0021] Several fibrous negative electrodes coated with the gel electrolyte are fixed by inserting their ends into corresponding holes on the first mounting plate and the second mounting plate. Several fibrous positive electrodes coated with the gel electrolyte are fixed by inserting their ends into corresponding holes on the first mounting plate and the second mounting plate. One end of the fibrous negative electrode protrudes from the hole in the first mounting plate, and one end of the fibrous positive electrode protrudes from the hole in the second mounting plate. The first mounting plate and the second mounting plate are arranged at intervals relative to each other, and the first mounting plate and the second mounting plate are provided with corresponding holes.
[0022] The first mounting plate and the second mounting plate are driven to rotate in opposite directions around the central axis, causing the plurality of fibrous negative electrodes and the plurality of fibrous positive electrodes to twist and wind around the central axis to form the bundle structure.
[0023] In one or more embodiments, the step of fixing the two ends of a plurality of fibrous negative electrodes coated with the gel electrolyte into corresponding insertion holes on a first mounting plate and a second mounting plate, and fixing the two ends of a plurality of fibrous positive electrodes coated with the gel electrolyte into corresponding insertion holes on the first mounting plate and the second mounting plate, includes:
[0024] A fiber core is formed by arranging one of the fiber-shaped positive electrodes or the fiber-shaped negative electrodes at the center of the first mounting plate and the second mounting plate;
[0025] A plurality of the fibrous negative electrodes are arranged in at least one concentric annular negative electrode structure surrounding the fiber core, and a plurality of the fibrous positive electrodes are arranged in at least one concentric annular positive electrode structure surrounding the fiber core, wherein the annular negative electrode structure and the annular positive electrode structure are arranged alternately.
[0026] In one or more embodiments, the encapsulation layer includes an inner PCNs insulating layer and an outer PVA protective layer.
[0027] To achieve the above objectives, another technical solution adopted in this application is:
[0028] A high-capacity flexible fibrous zinc-ion battery prepared by the preparation method described in any of the above embodiments is provided.
[0029] The advantages of this application, which differ from existing technologies, are:
[0030] 1. This application uses bromine to modify carbon nanotube fibers, which effectively improves the conductivity and mechanical strength of carbon nanotube fibers, and helps to improve the battery capacity.
[0031] 2. This application enables the gel electrolyte to be used as an electrolyte in aqueous zinc-ion batteries by coating the surface of carbon nanotube fibers loaded with negative electrode active material and carbon nanotube fibers loaded with positive electrode active material. This allows the battery to have both conductivity and bending performance, further improving the safety and service life of the battery.
[0032] 3. This application utilizes a fibrous negative electrode coated with gel electrolyte, which is twisted and wound together to form a bundle structure. This maximizes battery density, effectively increases battery capacity, and ensures safety, achieving an output of 258 mAh·g. -1 Specific capacity. Attached Figure Description
[0033] Figure 1 This is a schematic flowchart of one embodiment of the preparation method of the high-capacity flexible fibrous zinc-ion battery of this application;
[0034] Figure 2 yes Figure 1 A flowchart of one embodiment corresponding to step S500;
[0035] Figure 3 yes Figure 2 A schematic diagram of the state corresponding to step S501;
[0036] Figure 4 yes Figure 2 A schematic diagram of the state corresponding to step S502;
[0037] Figure 5 This is a cross-sectional structural schematic diagram of one embodiment of the bundle structure of this application;
[0038] Figure 6 This is a cross-sectional structural schematic diagram of one embodiment of the high-capacity flexible fibrous zinc-ion battery of this application. Detailed Implementation
[0039] The present application will now be described in detail with reference to the embodiments shown in the accompanying drawings. However, these embodiments do not limit the present application, and any structural, methodological, or functional modifications made by those skilled in the art based on these embodiments are included within the scope of protection of this application.
[0040] As mentioned in the background section, existing zinc-ion batteries use a traditional structural arrangement and have low capacity, which cannot meet the increasing demand for flexible wearable devices.
[0041] To improve the capacity of zinc-ion batteries, the applicant has developed a high-capacity fibrous zinc-ion battery with ultra-high specific capacity and excellent flexibility and mechanical properties.
[0042] Specifically, please refer to Figure 1 , Figure 1 This is a schematic flowchart of one embodiment of the preparation method of the high-capacity flexible fibrous zinc-ion battery of this application.
[0043] The preparation method includes:
[0044] S100. Modified carbon nanotube fibers are obtained by modifying carbon nanotube fibers with bromine.
[0045] Carbon nanotube fibers are used as carriers for flexible negative and positive electrodes. Firstly, bromine treatment can be used to improve the conductivity and mechanical strength of the carbon nanotube fibers.
[0046] S200: A negative electrode active material is electrodeposited on the surface of modified carbon nanotube fibers to obtain a fibrous negative electrode.
[0047] Using bromine-treated modified carbon nanotube fibers as a carrier, negative electrode active materials are deposited on the surface of the modified carbon nanotube fibers by electrodeposition.
[0048] Specifically, in one embodiment, the negative electrode active material can be zinc metal, and the electrodeposition method can include:
[0049] Modified carbon nanotubes are immersed in an electrolyte solution containing zinc sulfate and sodium sulfate, and zinc metal is deposited on the surface of the modified carbon nanotubes under the action of an external electric field to obtain a fibrous negative electrode.
[0050] The concentration of zinc sulfate in the electrolyte solution can be 0.5–3 mol / L, the concentration of sodium sulfate can be 0.1–1 mol / L, and the current density of the external electric field can be -10 to -50 mA / cm². 2 .
[0051] S300: A fibrous positive electrode is obtained by depositing positive electrode active material on the surface of modified carbon nanotube fibers using a hydrothermal method.
[0052] Using bromine-treated modified carbon nanotube fibers as a carrier, a positive electrode active material was loaded onto the surface of the modified carbon nanotube fibers using a hydrothermal method.
[0053] Specifically, in one embodiment, the positive electrode active material can be a manganese dioxide positive electrode material, and the hydrothermal deposition method can include:
[0054] An aqueous solution containing potassium permanganate and concentrated hydrochloric acid was added to a high-pressure reactor. The modified carbon nanotubes were then immersed in the aqueous solution and reacted in an oven. After the reaction was completed, the mixture was cooled to room temperature and then washed and dried sequentially to obtain carbon nanotube fibers loaded with positive electrode active material.
[0055] The aqueous solution contains potassium permanganate at a mass concentration of 1–10 g / L, concentrated hydrochloric acid at a volume concentration of 0.3–5.1%, and the reaction temperature in the oven is 60–80 °C for 15–60 min.
[0056] S400, a gel electrolyte is coated on the surface of the fibrous negative electrode and the fibrous positive electrode respectively.
[0057] Gel electrolytes are functional polymer materials with a three-dimensional polymer network structure. They are loosely cross-linked polymer materials containing a small amount of solid components. Gel electrolytes contain a large amount of water, making them soft and elastic.
[0058] By coating the surface of the negative electrode active material and the positive electrode active material with gel electrolyte, the gel electrolyte can be used as an electrolyte in aqueous zinc-ion batteries, which can make the battery have both conductivity and bending performance, thereby further improving the safety and service life of the battery.
[0059] Specifically, in one embodiment, the gel electrolyte can be a sodium carboxymethyl cellulose-zinc sulfate mixed solution, wherein the concentration of sodium carboxymethyl cellulose in the gel electrolyte is 0.05-0.2 g / mL, and the concentration of zinc sulfate is 0.1-0.3 g / mL.
[0060] S500: Several fibrous negative electrodes and several fibrous positive electrodes are twisted and intertwined to form a bundle structure.
[0061] The bundle structure includes a first end and a second end arranged opposite to each other, with one end of at least one fibrous positive electrode extending out of the first end to form a positive electrode connector, and one end of at least one fibrous negative electrode extending out of the second end to form a negative electrode connector.
[0062] Understandably, by twisting and entwining fibrous negative electrodes coated with gel electrolyte to form a bundle structure, the battery density can be maximized, the battery capacity can be effectively improved, and safety can be guaranteed.
[0063] Among them, the fibrous positive electrode can extend part of the bundle structure as a positive electrode connector, and the fibrous negative electrode can extend part of the bundle structure as a negative electrode connector.
[0064] Specifically, please refer to Figure 2 , Figure 2 yes Figure 1 A flowchart of one embodiment corresponding to step S500.
[0065] Methods for twisting and winding fibrous negative and positive electrodes may include:
[0066] S501. Insert the two ends of several fibrous negative electrodes coated with gel electrolyte into the corresponding holes on the first mounting plate and the second mounting plate respectively and fix them. Insert the two ends of several fibrous positive electrodes coated with gel electrolyte into the corresponding holes on the first mounting plate and the second mounting plate respectively and fix them.
[0067] The first mounting plate and the second mounting plate are arranged at intervals relative to each other, and the first mounting plate and the second mounting plate are provided with corresponding insertion holes.
[0068] Please see Figure 3 , Figure 3 yes Figure 2 A schematic diagram of the state corresponding to step S501. As shown in the figure, the first mounting plate 10 and the second mounting plate 20 are arranged opposite to each other, and the fibrous negative electrode 40 and the fibrous positive electrode 50 can be arranged in parallel and spaced apart through the corresponding insertion holes 30 on the first mounting plate 10 and the second mounting plate 20.
[0069] One end of the fibrous negative electrode 40 can extend from the insertion hole 30 of the first mounting plate 10 as a negative electrode connector 60; one end of the fibrous positive electrode 50 extends from the insertion hole of the second mounting plate 20 as a positive electrode connector 70.
[0070] S502, drive the first mounting plate and the second mounting plate to rotate around the central axis in opposite directions, so that a number of fibrous negative electrodes and a number of fibrous positive electrodes twist and wrap around the central axis to form a bundle structure.
[0071] After the fibrous negative electrode and the fibrous positive electrode are installed, the first mounting plate and the second mounting plate can be rotated in opposite directions, so that the fibrous negative electrode and the fibrous positive electrode twist and wind around the central axis.
[0072] Please see Figure 4 , Figure 4 yes Figure 2 A schematic diagram of the state corresponding to step S502.
[0073] In one embodiment, to optimize the structural layout, the fibrous negative electrode and the fibrous positive electrode can be arranged sequentially from the inside out. Specifically, the method of fixing the two ends of a plurality of fibrous negative electrodes and a plurality of fibrous positive electrodes into corresponding insertion holes in the first mounting plate and the second mounting plate respectively can include:
[0074] A fiber-shaped positive electrode or a fiber-shaped negative electrode is arranged at the center of the first mounting plate and the second mounting plate to form a fiber core.
[0075] A plurality of fibrous negative electrodes are arranged in at least one concentric annular negative electrode structure surrounding a fiber core, and a plurality of fibrous positive electrodes are arranged in at least one concentric annular positive electrode structure surrounding a fiber core, wherein the annular negative electrode structure and the annular positive electrode structure are arranged alternately.
[0076] Please see Figure 5 , Figure 5 This is a cross-sectional view of one embodiment of the bundle structure of this application. As shown in the figure, after adopting the above-described fixing method, the interior of the bundle structure after twisting is a multi-layered structure with 40 layers of fibrous negative electrode and 50 layers of fibrous positive electrode arranged alternately, which helps to improve the battery capacity.
[0077] In other embodiments, the fibrous negative electrode and the fibrous positive electrode can also adopt other layouts, all of which can achieve the effect of the technical solution of this application.
[0078] S600: A high-capacity flexible fibrous zinc-ion battery is obtained by covering the outer surface of the bundle structure with an encapsulation layer.
[0079] After the twisting and winding is completed, an encapsulation layer can be wrapped around the bundle structure. In one embodiment, the encapsulation layer may include an inner PCNs insulating layer and an outer PVA protective layer; in other embodiments, the encapsulation layer may also use other types of materials, which can be selected based on the actual working conditions.
[0080] Please see Figure 6 , Figure 6 This is a cross-sectional structural schematic diagram of one embodiment of the high-capacity flexible fibrous zinc-ion battery of this application.
[0081] As shown in the figure, the fibrous negative electrode 40 and fibrous positive electrode 50 are uniformly distributed, and the spaces between the carbon nanotube fibers are filled with gel electrolyte 80. The winding of multiple fibers can significantly improve the battery capacity, which can output 258 mAh·g. -1 The specific capacity is high; at the same time, the carbon nanotubes are modified with bromine, which improves their mechanical properties and conductivity, ensuring the flexibility of the battery and effectively solving the problem of low capacity in traditional flexible zinc-ion batteries; the flexible battery is covered with a PCNs insulating layer 90 and a PVA protective layer 100 to ensure insulation and mechanical strength.
[0082] The foregoing description of this disclosure is provided to enable any person skilled in the art to implement or use this disclosure. Various modifications to this disclosure will be apparent to those skilled in the art, and the general principles applicable herein can be applied to other variations without departing from the scope of this disclosure. Therefore, this disclosure is not limited to the examples and designs described herein, but is consistent with the widest scope of the principles and novel features disclosed herein.
Claims
1. A method for preparing a high-capacity flexible fibrous zinc-ion battery, characterized in that, include: Modified carbon nanotube fibers were obtained by modifying carbon nanotube fibers with bromine. A negative electrode active material is electrodeposited on the surface of the modified carbon nanotube fibers to obtain a fibrous negative electrode; A positive electrode active material was deposited on the surface of the modified carbon nanotube fibers using a hydrothermal method to obtain a fibrous positive electrode. A gel electrolyte is coated onto the surfaces of the fibrous negative electrode and the fibrous positive electrode, respectively. A bundle structure is formed by twisting and winding several fibrous negative electrodes coated with the gel electrolyte and several fibrous positive electrodes coated with the gel electrolyte together. The bundle structure includes a first end and a second end arranged opposite to each other. One end of the fibrous positive electrode extends out of the first end to form a positive electrode connector, and one end of the fibrous negative electrode extends out of the second end to form a negative electrode connector. A high-capacity flexible fibrous zinc-ion battery is obtained by covering the outer surface of the bundle-like structure with an encapsulation layer. The twisting and winding method includes: The process involves fixing several fibrous negative electrodes coated with the gel electrolyte at both ends by inserting them into corresponding holes on a first mounting plate and a second mounting plate, and fixing several fibrous positive electrodes coated with the gel electrolyte at both ends by inserting them into corresponding holes on the first mounting plate and the second mounting plate. One end of each fibrous negative electrode extends out of a hole in the first mounting plate, and one end of each fibrous positive electrode extends out of a hole in the second mounting plate. Specifically, this includes: arranging one fibrous positive electrode or one fibrous negative electrode at the center of the first mounting plate and the second mounting plate to form a fiber core; arranging several fibrous negative electrodes in at least one concentric annular negative electrode structure surrounding the fiber core; and arranging several fibrous positive electrodes in at least one concentric annular positive electrode structure surrounding the fiber core. The annular negative electrode structure and the annular positive electrode structure are arranged alternately. The first mounting plate and the second mounting plate are spaced apart from each other, and the first mounting plate and the second mounting plate are provided with corresponding holes. The first mounting plate and the second mounting plate are driven to rotate in opposite directions around the central axis, causing the plurality of fibrous negative electrodes and the plurality of fibrous positive electrodes to twist and wind around the central axis to form the bundle structure.
2. The preparation method according to claim 1, characterized in that, The step of electrodepositing the negative electrode active material on the surface of the modified carbon nanotube fibers to obtain a fibrous negative electrode includes: The modified carbon nanotube fibers are immersed in an electrolyte solution containing zinc sulfate and sodium sulfate, and metallic zinc is deposited on the surface of the modified carbon nanotube fibers under the action of an external electric field to obtain the fibrous negative electrode.
3. The preparation method according to claim 2, characterized in that, The concentration of zinc sulfate in the electrolyte solution is 0.5~3 mol / L, the concentration of sodium sulfate is 0.1~1 mol / L, and the current density of the external electric field is -10~-50 mA / cm². 2 .
4. The preparation method according to claim 1, characterized in that, The step of depositing positive electrode active material on the surface of the modified carbon nanotube fibers using a hydrothermal method to obtain a fibrous positive electrode includes: An aqueous solution containing potassium permanganate and concentrated hydrochloric acid was added to a high-pressure reactor. The modified carbon nanotube fibers were then immersed in the aqueous solution and reacted in an oven. After the reaction was completed, the mixture was cooled to room temperature and then washed and dried sequentially to obtain a fibrous positive electrode.
5. The preparation method according to claim 4, characterized in that, The aqueous solution contains potassium permanganate at a mass concentration of 1-10 g / L and concentrated hydrochloric acid at a volume concentration of 0.3-5.1%. The reaction temperature in the oven is 60-80°C, and the reaction time is 15-60 min.
6. The preparation method according to claim 1, characterized in that, The gel electrolyte is a mixed solution of sodium carboxymethyl cellulose and zinc sulfate, wherein the concentration of sodium carboxymethyl cellulose in the gel electrolyte is 0.05~0.2 g / mL and the concentration of zinc sulfate is 0.1~0.3 g / mL.
7. The preparation method according to claim 1, characterized in that, The encapsulation layer includes an inner PCNs insulating layer and an outer PVA protective layer.
8. A high-capacity flexible fibrous zinc-ion battery prepared by any one of the preparation methods described in claims 1 to 7.
Citation Information
Patent Citations
Metal ion battery and preparation method thereof
CN109950639A
Aqueous zinc ion battery based on manganese dioxide / graphene and preparation method
CN110729518A